A RETROPROSPECTIVE STUDY ON DIAGNOSTIC EFFICACY OF ULTRASONOGRAPHY AND THYROID AUTOANTIBODIES IN COMPARISON TO HISTOPATHOLOGY IN DETECTION OF HASHIMOTOS THYROIDITIS. - Dr Rajeshwari Patil; Dr. Shivsharanappa akka; Dr. Priyanka akka (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Chronic thyroiditis, commonly referred to as Hashimoto's thyroiditis, is an autoimmune disorder characterized by lymhocytic infiltration of the thyroid gland, often leading to hypothyroidism. While histopathology remains the gold standard it can be done only post-surgery, hence serological testing for anti-thyroid antibodies (anti-TPO and anti-Tg) remains the easily preferred.  Recently ultrasound (USG) has gained increasing prominence due to its non-invasive nature, wide availability, and ability to detect structural gland changes that may precede or accompany autoimmune activity. Hence this study was undertaken to compare diagnostic efficacy of ultrasound in comparison to biochemical parameters in patients with Hashimotos thyroiditis with histopathlogy considered as gold standard diagnosis. Methodology: A retroprospective multicentre study was done in 100 patients diagnosed with hashimotos thyroiditis. Study period was 3 years (). Data was collected from electronic medical records after obtaining ethical committee and institutes approval. Data collected using questionnaire which consists of items on patient characteristics, Biochemical parameters,  Sonogrpahy assessment and histopathology finding. Sensitivity, specificity, disease prevalence, positive and negative predictive value as well as accuracy are expressed as percentages with 95% confidence intervals. ROC, to predict the best diagnostic test and AUC, to estimate the performance of the test. SPSS version 22 is used with P